Efektivitas WFH (Work from Home) saat Pandemi Covid-19 sebagai penunjang pemberian praktek ASI eksklusif secara direct breast feeding (DBF) pada ibu bekerja: Efektivitas WFH (Work From Home) saat Pandemi Covid-19 sebagai Penunjang Pemberian Praktek ASI Eksklusif secara Direct Breast Feeding (DBF) pada Ibu Bekerja - Megah Stefani (Universitas Airlangga, 2022)
Background: The work pattern that occurs during the pandemic is working from home (Work from Home). Before the pandemic, breastfeeding mothers who worked normatively had the right to leave for three months. This regulation often becomes an obstacle for breastfeeding mothers who work to practice exclusive breastfeeding for 6 months using Direct Breast-Feeding (DBF). Objectives: This study aims to analyze the effectiveness of WFH on the implementation of exclusive breastfeeding with DBF in working mothers. Methods: The research design is a retrospective case control. The subject category was divided into two treatments: full WFH mothers and partial WFH mothers. The subject treatment groups were divided based on the method of breastfeeding: direct breastfeeding (DBF) and mixed feeding (MF). The subjects of this study were 27 working mothers, 20 mothers as cases, and 7 mothers as controls which were determined purposively. Results: The difference test between the DBF breastfeeding method during the exclusive breastfeeding period and the WFH treatment showed a significant difference (p=0.000) between the partial WFH treatment and the choice of the exclusive breastfeeding method for DBF in infants. On the other hand, there was no significant difference (p=0.083) between the full WFH treatment and the choice of exclusive breastfeeding method for DBF in infants. The difference test between the WFH partial treatment and the DBF breastfeeding method during the exclusive breastfeeding period showed a significant difference (p=0.030). The difference test between the full WFH treatment and the DBF breastfeeding method during the exclusive breastfeeding period showed a significant difference (p=0.005). The mixed feeding method also showed that there were differences (p=0.000) in working mothers who were fully WFH. Conclusions: Full WFH affects the success of exclusive breastfeeding with the DBF method. Full WFH during the Covid-19 pandemic in breastfeeding mothers proved effective for implementing the practice of exclusive breastfeeding using the DBF method.